2018
DOI: 10.4103/ortho.ijortho_308_16
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Malleolus Fractures in Trimalleolar Ankle Fractures: Malleolus versus Transyndesmal Fixation

Abstract: Background:In ankle fractures involving the posterior malleolus, the issue of which types of fractures require posterior malleolus fixation is still controversial. Recent studies have demonstrated that trimalleolar fractures adversely affect the functional outcomes in comparison to bimalleolar fractures of the lateral and medial malleolus. The purpose of this study was to assess the effects of posterior malleolus fixation on the functional and radiological outcomes.Materials and Methods:Reduction quality, deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…Jaskulka et al [30] performed a 5-7 year follow-up study of 142 patients with ankle fractures, and suggested that if fixation was not performed, long-term results were significantly poor, even in patients with a small marginal fragment of the lip of the tibia. Tosun et al [31] showed that the fixation of PMF is closely related to the successful radiological and functional outcomes of trimalleolar fracture. After PMF is fixed, transyndesmal screw fixation may not be required.…”
Section: Discussionmentioning
confidence: 99%
“…Jaskulka et al [30] performed a 5-7 year follow-up study of 142 patients with ankle fractures, and suggested that if fixation was not performed, long-term results were significantly poor, even in patients with a small marginal fragment of the lip of the tibia. Tosun et al [31] showed that the fixation of PMF is closely related to the successful radiological and functional outcomes of trimalleolar fracture. After PMF is fixed, transyndesmal screw fixation may not be required.…”
Section: Discussionmentioning
confidence: 99%
“…However, a lot of recent literature argue that surgical xation of small fragments of the posterior malleolus may have a better effect on the clinical effects [8,13,15]. And also, posterior malleolus xation relates to syndesmotic stability [14,[28][29][30]. Then it may allow an opportunity to avoid standard syndesmotic xation with screws, which bring about many complications [31].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of the posterior malleolus fractures was reported to be 7% to 44% of all ankle fractures. These types of fractures classically include the Volkmann tubercle of the posteromedial tibial plafond [18,19]. Biomechanical studies suggest that the posterior malleolus serves as an important contributor to the stability of ankle joint, while the indication of surgical treatment remains controversial [20].…”
Section: Posterior Malleolus Fracturesmentioning
confidence: 99%